Association of renin-angiotensin and endothelial nitric oxide synthase gene polymorphisms with blood pressure progression and incident hypertension: prospective cohort study - Conen, David; Glynn, Robert J; Buring, Julie E; Ridker, Paul M; Zee, Robert Y L (Journal of hypertension, 2008)
The renin-angiotensin system and endothelial function have both been associated with hypertension. The aim of the present study was to assess the relationship of six previously characterized gene variants in the renin-angiotensin system and the NOS3 gene with blood pressure progression and incident hypertension. We analyzed data from 18 436 Caucasian women who participated in a prospective cohort study and were free of hypertension at baseline. Six previously characterized single nucleotide polymorphisms (NOS3 rs1800779, NOS3 rs3918226, NOS3 rs1799983, ACE rs1799752, AGT rs699, and AGTR1 rs5186) were genotyped. Blood pressure progression at 48 months and incident hypertension during the entire follow-up according to the different genotypes and inferred haplotypes were assessed by logistic regression and Cox proportional hazards models, respectively. At 48 months, 47.4% of the women had blood pressure progression. The odds ratios (95% confidence intervals) for blood pressure progression associated with NOS3 rs1800779, NOS3 rs3918226, NOS3 rs1799983, ACE rs1799752, AGT rs699, and AGTR1 rs5186 were 1.00 (0.96-1.05), 1.00 (0.92-1.09), 0.99 (0.94-1.04), 0.96 (0.92-1.01), 1.04 (0.99-1.08), and 1.03 (0.98-1.08), respectively. During 9.8 years of follow-up, 29.6% of women developed incident hypertension. The hazard ratios (95% confidence interval) for the six polymorphisms were 1.01 (0.97-1.06), 1.06 (0.99-1.14), 1.05 (1.01-1.09), 0.99 (0.95-1.02), 1.01 (0.97-1.05), and 0.99 (0.95-1.04). NOS3 haplotypes were not significantly associated with blood pressure progression (P = 0.91) or incident hypertension (P = 0.10). Blood pressure progression and incident hypertension are not consistently associated with six well-characterized genetic polymorphisms of the renin-angiotensin system and the NOS3 gene in a large cohort of Caucasian women.